Opioids stimulate growth hormone (GH) release in man independently of GH-releasing hormone. - Delitala, G; Tomasi, P; Palermo, M; Ross, R; Grossman, A; Besser, G (1989)
The Met-enkephalin analog DAMME [D-Ala2,MePhe4-Met-enkephalin-(o)-o1, FK 33-824] can stimulate GH secretion in man. In this study we investigated the effects of the guanyl derivative of DAMME (G-DAMME) on the serum GH response to an analog of GHRH in normal men. GHRH-(1-29)NH2 and G-DAMME each induced a rise in serum GH, and the increase was greater when both were given together. Since the GHRH-(1-29)NH2 dose (100 micrograms) used was a maximally stimulatory one, these results suggest that the enhancing effect of G-DAMME on GHRH-induced GH release may be mediated through inhibition of somatostatin release.